2020
DOI: 10.1101/2020.03.21.20040360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of C-reactive protein in patients with COVID-19

Abstract: Background Elevated serum C-reactive protein (CRP) level was observed in most patients with .Methods Data of COVID-19 patients with clinical outcome in a designated hospital in Wuhan, China, were retrospectively collected and analyzed from Jan 30 to Feb 20, 2020. The prognostic value of admission CRP was evaluated in patients with COVID-19. ResultsOut of 298 patients enrolled, 84 died and 214 recovered. Most non-survivors tended to be males, old aged, or with chronic diseases. Compared to survivors, non-surviv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 20 publications
9
70
1
5
Order By: Relevance
“…Higher CRP level has been reported as positively related to the severity of lung injury and COVID-19 severity by other researchers (12,13). However, in our study, no signi cant correlation between plasma CRP level and the risk of initial GI involvement has been found in this study ( Table 1).…”
Section: Correlation Between Clc and Initial Gi Involvementcontrasting
confidence: 74%
“…Higher CRP level has been reported as positively related to the severity of lung injury and COVID-19 severity by other researchers (12,13). However, in our study, no signi cant correlation between plasma CRP level and the risk of initial GI involvement has been found in this study ( Table 1).…”
Section: Correlation Between Clc and Initial Gi Involvementcontrasting
confidence: 74%
“…Only in this way, can medical staffs make greater use of limited medical resources and reduce mortality. Recent clinical data have indicated that lymphocyte [9,10], CRP [11] and other factors may be related to the severity of COVID-19 [6]. However, the role of ferritin seems to be ignored even though clinical observation has discovered the abnormal ferritin levels in severe COVID-19 patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, whether these changes and lipid pro les at admission can help to predict the clinical outcome of the COVID-19 patients remains unclear. C-reactive protein (CRP) is a common in ammatory marker, which increases in most patients with COVID-19 and is closely related to the severity of the disease [22]. And HDL and Apo-AI display pleiotropic properties including anti-oxidant and anti-in ammatory functions [9].Therefore, the ratio of CRP/HDL-C or CRP/ Apo-AI may re ect the balance between pro-in ammatory and anti-in ammatory process.…”
Section: Introductionmentioning
confidence: 99%